Hydrodynamic Studies during Gas‐Solid Conveying in a Vertically Upward Converging Riser Tube‡. Issue 3 (15th January 2022) - Ghosh, Tanushree; Sarkar, Jyotiprakas; Sadhukhan, Anup Kumar; Barman, Sanghamitra
Abstract: Experimental and theoretical investigations on hydrodynamics for gas‐solid particles flow were carried out in a vertical upward converging pneumatic conveying system. One‐dimensional mathematical modeling and simulation were done using the FORTRAN‐95 program. The influence of convergence geometry on the hydrodynamic parameters like particle velocity, gas‐particle slip velocity, pressure drop, and particle Reynolds number ( Re p ) along the riser were studied. Experiments were conducted using the dilute phase mode with three types of granular cereal seeds of different sizes. Some significant differences in all hydrodynamic parameter profiles along the riser were observed between converging and uniform risers. Enhancement of Re p in the converging riser implies a higher gas‐solid transfer coefficient. Abstract : The hydrodynamics for gas‐solids particle flow in a vertical upward converging pneumatic conveying system were experimentally and theoretically investigated. The impact of convergence geometry on the hydrodynamic parameters in terms of particle velocity, gas‐particle slip velocity, pressure drop, and particle Reynolds number along the riser height during the gas‐solids particle flow was evaluated.